Experiência discente com o cuidado a paciente portador de Epidermodisplasia Verruciforme - Correa, Bruna Maria Cinel [UNESP]; Bolgue, Ana Paula Munhoz [UNESP]; Oliveira, Ana Paola Piloto De [UNESP]; Ayres, Jairo Aparecido [UNESP]; Paiva, Bianca Sakamoto Ribeiro (Associação Brasileira de Enfermagem, 2013)
Report of an experience of nursing students in providing care to a patient with epidermodysplasia verruciformis, during the internship in the discipline Nursing in Transmittable Diseases, at the dermatology ward of a teaching hospital, located in the state of São Paulo, Brazil, in 2009. This is a rare genodermatosis, susceptible to infection with different types of human papilloma viruses, that cause exacerbated physical changes that impact the psyche of the affected individual. Care delivery was based on the assistance complexity indicated by the application of the Patient Classification System proposed by Perroca. The experience allowed students to learn how to cope with a patient affected by a rare and complex disease, of difficult resolution, and to provide integral care to this individual, perceiving him beyond the lesions. One conclude that the experience has greatly contributed to the growth of the students as future professionals.

Relato de experiência de situação vivenciada, em 2009, por acadêmicas de enfermagem, durante estágio da disciplina Enfermagem em Doenças Transmissíveis, na enfermaria de dermatologia de um hospital de ensino do interior paulista, em que cuidaram de um paciente com Epidermodisplasia Verruciforme. Esta é uma genodermatose rara, com susceptibilidade à infecção por diferentes tipos de papiloma vírus humanos, ocasionando alterações físicas exacerbadas e impactando o psiquismo da pessoa acometida. A assistência foi baseada na complexidade assistencial indicada pela aplicação do Sistema de Classificação de Pacientes proposto por Perroca. A experiência proporcionou aprendizado no cuidado a paciente portador de doença rara, complexa e de difícil resolução, possibilitando a necessidade de assisti-lo integralmente, percebendo-o além das lesões. Conclui-se que este tipo de experiência muito contribuiu para o crescimento das acadêmicas como futuras profissionais de enfermagem.

Relato de experiencia vivida por estudiantes de enfermería, en 2009, durante la pasantía de la disciplina de Enfermería en Enfermedades Transmisibles, en la sala de dermatología de un hospital universitario del estado de São Paulo, Brasil, donde cuidarán a uno paciente con Epidermodisplasia Verruciforme. Esta es una genodermatosis rara, con susceptibilidad para la infección por diferentes tipos de virus del papiloma humano, causando cambios físicos exasperados e impacto en la psiquis de la persona afectada. La asistencia esté basada en la complejidad de la atención, segundo la aplicación del Sistema de Clasificación de Pacientes propuesto por Perroca. A experiencia proporciono aprendizaje en el cuidado del paciente con una enfermedad rara, compleja y de difícil cura, dando la posibilidad a las estudiantes de asistirlo integralmente, más allá de las lesiones. Concluye-se que este tipo de experiencia contribuyó para el crecimiento de las estudiantes como futuros profesionales.
Experiencia de estudiantes con el cuidado a paciente con Epidermodisplasia Verruciforme
Student experience in providing care to a patient with Epidermodysplasia Verruciformis
Keywords: Enfermagem; Epidermodisplasia Verruciforme; Cuidados de Enfermagem; Nursing; Epidermodysplasia Verruciformis; Nursing Care